PAUD Inklusif: Efikasi Diri dan Tingkat Literasi Guru Memengaruhi Kemampuan Merancang Individualized Education Program (IEP)? - Siron, Yubaedi (Al-Athfal: Jurnal Pendidikan Anak, 2020)
The ability to create an Individualized Education Program (IEP) for inclusive Early Childhood Education (ECE) teachers is a matter that needs to be further studied. At present, there are still many teachers who still need to be prepared with sufficient knowledge to create a proper IEP. The ability to create an ideal IEP can be useful for teachers in the implementation of an ideal inclusive ECE. An ideal inclusive ECE can serve as an indicator of the quality of education of a nation. The objective of this research is to analyze the effect of teacher's self-efficacy and teacher's literacy on Education for Children with Special Needs on the ability to design an IEP. The study uses a path analysis involving 50 ECE teachers from 50 different schools in East Jakarta. This study applied a simple random sampling technique to involve teachers. The results of this study revealed: 1) There was no direct effect on teacher self-efficacy towards the ability to design an IEP; 2) There was a direct effect on teacher literacy towards the ability to make an IEP; 3) There was no direct effect on teacher's self-efficacy towards the teacher's literacy on Education for Children with Special Needs.